Extended coagulation profile of children with Long Covid: a prospective study - Di Gennaro, Leonardo; Valentini, Piero; Sorrentino, Silvia; Ferretti, Maria Antonietta; De Candia, Erica; Basso, Maria; Lancellotti, Stefano; De Cristofaro, Raimondo; De Rose, Cristina; Mariani, Francesco; Morello, Rosa; Lazzareschi, Ilaria; et al. (Scientific reports, 2022)
Emerging data suggests that endotheliopathy changes can be associated with post covid condition (PCC) in adults. Research on the matter in children is lacking. We analyzed an extended coagulation profile including biomarkers of endothelial damage in children with PCC and compared it with a control group of children that fully recovered post- SARS-CoV-2 infection. A case-control study enrolling children below 18 years of age with previous microbiologically confirmed SARS-CoV-2 infection in a pediatric post-covid unit in Italy ≥ 8 weeks after the initial infection. Samples were taken at 8 and 12 weeks after the SARS-CoV-2 diagnosis and analyzed for coagulation profiling (fibrinogen, prothrombin time, international normalized ratio, activated partial thromboplastin time, d-dimers, factor VIII coagulant activity, plasma von Willebrand factor (VWF) antigen and VWF ristocetin cofactor (RC)). We compared coagulation profiles in samples from children identified with PCC (at least one, or three or more symptoms, which could not be explained by an alternative diagnosis, at the 8- and 12-week follow-up assessment using the pediatric Long Covid International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC) survey. Seventy-five children were enrolled, 49.3% were females, the median age was 10.2 (IQR 4.9) years. Forty-six (61%) of the children had at least one persisting symptom at the eight weeks post-onset, (PCC8); 39/75 (52%) had persistent symptoms for more than 12 weeks (PCC12) and 15/75(32%) had at least three persisting symptoms (PCC ≥ 3) at 12 weeks. Children with PCC presented more frequently with abnormal D-Dimer levels above the reference range compared to children that had fully recovered at the 8–12 weeks (39.1% vs. 17.2%, p = 0.04), and 12 week follow up or more (41% vs. 17.2%, p = 0.05), and in children with three or more symptoms at 12 weeks follow up compared to those that had recovered (64.3% vs. 22.2%, p = 0.002). For the other coagulation profiles, there were abnormal values detected for VWF, FVIII, RC and Fibrinogen but no significant differences between children with PCC compared to controls. Although the majority of children in our cohort showed coagulation profile within or close to normal ranges, we found that a higher proportion of children with PCC, and specifically those with a more severe spectrum characterized with three or more persisting symptoms, had abnormal D-dimer levels compared to other children that fully recovered from an acute SARS-CoV-2 infection.